2022
DOI: 10.1111/cns.13984
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion along perivascular spaces provides evidence interlinking compromised glymphatic function with aging in Parkinson's disease

Abstract: Aims The aim of the study was to evaluate the glymphatic function and its related factors in patients with Parkinson's disease (PD) and patients with PD of different ages using the diffusion tensor image analysis along the perivascular space (DTI‐ALPS) method. Methods Medical records and imaging data of 93 patients with idiopathic PD and 42 age‐ and sex‐matched healthy controls (HCs) were retrospectively reviewed and analyzed. The diffusivity along the perivascular spaces, projection fibers, and association fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
(122 reference statements)
3
23
0
Order By: Relevance
“…The DTI‐ALPS index and age/duration of epilepsy showed significant correlations in the present study. The decline in glymphatic system function with age was consistent with the results of several previous studies [42, 43]. With regard to the glymphatic system, sleep quality shows a notable decline with normal aging.…”
Section: Discussionsupporting
confidence: 91%
“…The DTI‐ALPS index and age/duration of epilepsy showed significant correlations in the present study. The decline in glymphatic system function with age was consistent with the results of several previous studies [42, 43]. With regard to the glymphatic system, sleep quality shows a notable decline with normal aging.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we conducted correlation analysis by treating the ALPS index as a continuous variable to investigate the interlink between baseline glymphatic neuroimaging indicators and the longitudinal changes in clinical PD symptoms, which further validated the predictive role of the glymphatic system. Still, ALPS index was an indirect and regional biomarker measuring glymphatic activity in the basal ganglion area 13 . As such, we should interpret the association between glymphatic function and longitudinal changes in clinical PD symptoms cautiously, and whether glymphatic dysfunction involved in the progression requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Still, ALPS index was an indirect and regional biomarker measuring glymphatic activity in the basal ganglion area. 13 As such, we should interpret the association between glymphatic function and longitudinal changes in clinical PD symptoms cautiously, and whether glymphatic dysfunction involved in the progression requires further investigation. However, recent study showed that the ALPS index was highly correlated with classical glymphatic function measured by glymphatic MRI, 14 and it has widely been used as an imaging indicator of whole-brain glymphatic function in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, diffusion tensor image analysis along the perivascular space (DTI-ALPS) has emerged as an alternative non-invasive method for evaluating the glymphatic function in human brain ( 5 , 16 ). Several studies have reported the ability of the DTI-ALPS method to characterize glymphatic function in PD patients, and the lower ALPS index may reflect impairment of the glymphatic system ( 17 - 19 ).…”
Section: Introductionmentioning
confidence: 99%